Innovation in an authoritarian society: China during the pandemic crisis. Issue 2 (4th January 2021) - Xiong, Jie; Yan, Jie; Fu, Kun; Wang, Ke; He, Yuanqiong
Abstract : Purpose: This paper aims to understand the role of government played in the innovation process during the social crisis, and to investigate the innovation activities of the authoritarian state when dealing with social crisis. Design/methodology/approach: Secondary data pertaining to eight impactful technological innovations in China during the COVID-19 crisis reveal how interactions and joint efforts by commercial firms and government organizations emerged as spontaneous responses. Findings: The analysis of eight innovations – health code adoption, health omnichannel construction, noncontact service provision, distance education provision, public emotion consolation service, cross-boundary project promotion, cloud office adoption and medical material production – reveals a matrix of best practices that details the roles of government (controller or endorser) and the value creation orientation (pro-social or pro-economic value). Originality/value: This study enriches innovation literature by providing a new perspective on the relationship between governmental force and technological innovation during social crises. As these new insights reveal, technological innovation can contribute to social crisis management. China's example provides helpful implications for other countries suffering from the COVID-19 crisis.